Viabilidad de semillas pretratadas de Caesalpinia velutina (B & R) Standl; Enterolobium cyclocarpum (J.) Griseb. y Leucaena leucocephala (Lam.) de Wit - Buch, M.S.; Jara, L.F.; Franco, E. (CATIE, Turrialba (Costa Rica), 2015)
6 fig. 5 tab.